Oral Bioavailability and Lymphatic Transport of Pueraria Flavone-Loaded Self-Emulsifying Drug-Delivery Systems Containing Sodium Taurocholate in Rats - Jin Qiao; Danyang Ji; Shilin Sun; Guangyuan Zhang; Xin Liu; Bingxue Sun; Qingxiang Guan (MDPI AG, 2018)
We developed self-microemulsifying drug-delivery systems (SMEDDS), including bile salts, to improve the oral bioavailability of pueraria flavones (PFs). The physical properties of the SMEDDS using Cremophor RH 40, and bile salts as mixed surfactants at weight ratios of 10:0–0:10 were determined. The particle sizes of PFs-SMEDDSNR containing sodium taurocholate (NaTC) and Cremophor RH 40, and PFs-SMEDDSR containing Cremophor RH 40 were measured upon dilution with deionized water and other aqueous media. Dilution volume presented no remarkable effects on particle size, whereas dilution media slightly influenced particle size. PFs-SMEDDSNR and PFs-SMEDDSR provided similar release rates in pH-1.2 hydrochloride solution. However, the release rate of PFs-SMEDDSNR was faster than that of PFs-SMEDDSR in pH-6.8 phosphate buffer containing 20 mM NaTC and 500 U/mL porcine pancreas lipase. The pharmacokinetics and bioavailability were measured in rats. The oral bioavailability of PFs-SMEDDSNR was 2.57- and 2.28-fold that of a suspension of PFs (PFs-suspension) before and after the blockade of the lymphatic transport route by cycloheximide, respectively. These results suggested PFs-SMEDDSNR could significantly improve the oral relative absorption of PFs via the lymphatic uptake pathway. SMEDDS containing NaTC may provide an effective approach for enhancing the oral bioavailability of PFs.